Project 2B: Shapes into planes / Anis Zulfah Zulkifli - Zulkifli, Anis Zulfah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
This project is a continuation of the previous project. The shapes extracted from the basic motifs on the columns and is arranged in a linear manner. The organisation resembles the harmony in flora surrounding the house. The dark to light colour mimics the way the columns rise from the ground, standing tall safeguarding the house from harm.